2020
DOI: 10.32598/ijmtfm.v10i1.26253
|View full text |Cite
|
Sign up to set email alerts
|

Determining Undeclared Synthetic Pharmaceuticals as Adulterants in Weight Loss Herbal Medicines

Abstract: Background: The popularity and use of herbal medicines and supplements are growing worldwide. Herbal anti-obesity products have been considered as suitable alternatives to synthetic pharmaceuticals as they are introduced as harmless natural products. However, some manufacturers often add undeclared synthetic pharmaceuticals to the anti-obesity herbal medicine products to improve their efficacy and potency. The present study aimed to analyze herbal weight loss products collected from the drug market in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A 20-μL sample was injected into the column and eluted at room temperature with a flow rate of 1.0 mL/min. The result showed herbal products brand (cravil) contain medicinal chemicals (caffeine) 86 .…”
Section: Issn: 2320-4850 [35] Coden (Usa): Ajprhsmentioning
confidence: 99%
“…A 20-μL sample was injected into the column and eluted at room temperature with a flow rate of 1.0 mL/min. The result showed herbal products brand (cravil) contain medicinal chemicals (caffeine) 86 .…”
Section: Issn: 2320-4850 [35] Coden (Usa): Ajprhsmentioning
confidence: 99%
“…Studies found that many HMs that are used for weight reduction, weight gain, sexual enhancements and analgesia are adulterated with known chemical and pharmaceutical agents. [12][13][14][15] Therefore, it is necessary to assess HMs and dietary supplements to determine their contents, efficacy, and safety profiles. 16,17…”
Section: Herbal Medicinesmentioning
confidence: 99%
“…The use of synthetic stimulants was developed to treat patients who have Parkinson's disease, obesity, and depression [14,132,133]. More recently, they have been used as cognitive enhancers (commonly used by students or professionals who need to focus when working in stressful environments), to enhance athletes' performance and to help people lose weight [14,134,135]. The use of synthetic stimulants during sexual practices with multiple partners to enhance sexual performance, commonly without protection, potentiates the transmission of sexual diseases [14,136].…”
Section: Warning Signs Of New Psychoactive Substance Abusementioning
confidence: 99%